Village Financial Accountability Model with Community Participation as Moderation in Village Government in South Sumatra Province - Rudi Ananda; Afrizal Afrizal; Sri Rahayu (Greenation International Journal of Economics and Accounting, 2026)
The low level of village financial accountability, often marked by budgetary deviations, is a critical issue in South Sumatra Province. This study aims to analyze the influence of internal control, transparency, integrity, and organizational commitment on village financial accountability, and to examine the role of community participation as a moderating variable. Employing a quantitative approach, the data were analyzed using Moderating Regression Analysis (MRA) to test the research hypotheses. The results indicate that only internal control has a positive and significant influence on accountability. Conversely, transparency, integrity, and organizational commitment do not have a significant partial influence. In the moderation analysis, community participation has proven to strengthen the positive influence of integrity on accountability yet paradoxically weakens the positive influence of internal control. Meanwhile, community participation does not play a significant moderate role in the relationship between transparency and organizational commitment with accountability. This study concludes that strengthening the internal control system is a key factor in enhancing village financial accountability. Furthermore, community participation plays a complex role; it can act as an effective enhancer for the value of integrity, but it must be managed proportionally to avoid hindering existing formal oversight mechanisms.